Molecular basis for the mechanical response of sulfa drug crystals - SeethaLekshmi, Sunil (2021)
Comprehension of the nanomechanical response of crystalline materials requires the understanding of the elastic and plastic deformation mechanisms in terms of the underlying crystal structures. Nanoindentation data were combined with structural and computational inputs to derive a molecular-level understanding of the nanomechanical response in eight prototypical sulfa drug molecular crystals. The magnitude of the modulus, E, was strongly connected to the non-covalent bond features, that is, the bond strength, the relative orientation with the measured crystal facet and their disposition in the crystal lattice. Additional features derived from the current study are the following. Firstly, robust synthons well isolated by weak and dispersive interactions reduce the material stiffness; in contrast, the interweaving of interactions with diverse energetics fortifies the crystal packing. Secondly, mere observation of layered structures with orthogonal distribution of strong and weak interactions is a prerequisite, but inadequate, to attain higher plasticity. Thirdly, interlocked molecular arrangements prevent long-range sliding of molecular planes and, hence, lead to enhanced E values. In a broader perspective, the observations are remarkable in deriving a molecular basis of the mechanical properties of crystalline solids, which can be exploited through crystal engineering for the purposeful design of materials with specific properties.